Monitoring Changes in the Morphology and Storage of a Small Water Reservoir: A Case Study from Vrbovce, Slovakia - Výleta Roman; Valent Peter; Danáčová Zuzana (Slovak Journal of Civil Engineering, 2020)
One of the most profound problems in the operation of water reservoirs is their siltation by sediments coming from agricultural land. The siltation of water reservoirs can significantly shorten their life spans and prevent them from effectively fulfilling their functions. Therefore, accurate monitoring of the current state and dynamics of siltation processes is critical to maintaining their economic, environmental, and societal functions. This study presents a simple method to evaluate the sedimentation rate of a small water reservoir in Slovakia. The method is based on comparing the results from two bathymetric surveys that were carried out in 2017 and 2019 using an ultrasonic acoustic doppler current profiler (ADCP), which was originally developed to measure river discharges. A raster map of the thickness of the sediment in the reservoir was assembled by subtracting the two bathymetric surveys from each other. The analysis of the results showed that the mean annual sedimentation rate of the reservoir is only 101 m3/year, representing a mean increment in sediment thickness of 1.4 cm. The method described showed promising results and could be applied to numerous small water reservoirs of a similar size across Slovakia.